Executive Committee Minutes 2015-09-24 - Academic Senate:::::::::
Agenda – Approved. Minutes of 9/10/15 – Approved. Chair Report. Questions for the President. Provost Report. Vice Chair Report. Vice President of Student Affairs Report. Classroom upgrade group follow up. EPC Report. FSAC Report. CFA Report. Check in for EPC with projects referred by Executive Committee: Online/Hybrid Course Policy; APC-EPC task force on Schedule 25; Academic Certificate policy. Ad Hoc Committee for WASC – not approved. Faculty Retreat Topic discussion. Senate agenda approved.